2012
DOI: 10.4236/as.2012.37116
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analysis for choosing the main soil parameters of a crop model to be determined

Abstract: The use of a crop model like STICS for appropriate management decision support requires a good knowledge of all the parameters of the model. Among them, the soil parameters are difficult to know at each point of interest and costly techniques may be used to measure them. It is therefore important to know which soil parameters need to be determined. It can be stated that those which affect significantly the output variable deserve an accurate determination while those which slightly affect the model output vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The Nash-Sutcliffe efficiency showed a better agreement between the two simulation scenarios, as all outputs related to the soil module recorded an NSE over 0.85. Wilmott's index of the agreement also confirmed the agreement of the results of the PTF-based simulation with the measurement-based simulation for all soil module Similarly, Varella et al [25] showed a higher sensitivity of field capacity when simulating the growth and yield of wheat and sugar beet using the STICS model. Chen et al [76] also showed a higher sensitivity of wheat yield to the available water capacity.…”
Section: Functional Analysissupporting
confidence: 55%
See 3 more Smart Citations
“…The Nash-Sutcliffe efficiency showed a better agreement between the two simulation scenarios, as all outputs related to the soil module recorded an NSE over 0.85. Wilmott's index of the agreement also confirmed the agreement of the results of the PTF-based simulation with the measurement-based simulation for all soil module Similarly, Varella et al [25] showed a higher sensitivity of field capacity when simulating the growth and yield of wheat and sugar beet using the STICS model. Chen et al [76] also showed a higher sensitivity of wheat yield to the available water capacity.…”
Section: Functional Analysissupporting
confidence: 55%
“…Many studies have been conducted to evaluate the sensitivity of plant parameters and the management practices of different crops under different models [24,[37][38][39][40][41][42][43]. Although the sensitivity assessment of soil is essential [25], limited attention has been paid to evaluating the sensitivity of soil parameters [42]. Hence, this study aims to evaluate the sensitivity of soil parameters to the growth and yield of rice using the APSIM-Oryza model in APSIM 7.10.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of sensitivity analysis, this method is called screening or factor fixing ( [11], [13]). [55] and [62] describe an application to the crop model STICS.…”
Section: Sensitivity Analysismentioning
confidence: 99%